Prevalence and genotyping of African swine fever virus in apparently healthy pigs in Masaka, Mukono and Kamuli Districts in Uganda - Akol, Joyce (Makerere University, 2015)
African swine fever (ASF) is a viral hemorrhagic disease associated with death in infected pigs. African swine fever virus (ASFV) is a DNA virus that circulates in blood and lymphoid system of the pigs causing disease. There are various reports on ASF outbreaks in the country with a few confirmed in apparently healthy pigs which pigs show no signs of infection. Therefore a survey of apparently healthy pigs was undertaken to show the extent they habour the antibodies and antigen of ASFV and later determine the genetic diversity of the virus ASF in Kamuli, Mukono and Masaka districts of Uganda using serological, molecular and genotyping techniques. In total 1,192 blood and sera samples were collected and analyzed. All the pigs tested except one (1/1192) were negative for (ASFV) and none for antibodies indicating that ASFV causes a paracute / acute infection in Ugandan pigs with rare detection of virus or antibodies in apparently healthy pigs. Therefore chronically infected pigs are unlikely to be important in the epidemiology of ASF. The positive pig in Kamuli district was infected with genotype IX, the most common circulating ASFV genotype in Uganda. With one positive pig for ASFV, it was not possible to authoritatively associate predictors of infection with disease in tested pig farms. It is thus recommended that these predictors of infection with ASFV are studied in future ASF outbreak areas where the virus or antibodies in pigs may occur in high prevalence.